Lexical update: category-Directed search of state of the art dictionaries - Cabrera, Sandra; Pacheco Salazar, Vicente Guillermo
This thesis was designed to help students of the English language and people partiularly interested in the language, as well. It contains 6,775 new words classified in 265 etymological categories and 32 sub categories. Most words come along with pronunciation, the word, indeed, in context and of course where the word comes from. All these features will be very useful and good pieces of reference to anyone interested in improving and overcoming lack of vocabulary and pronuciation, as well